Constituents of the Essential Oils of Helichrysum graveolens (Bieb.) Sweet from Turkey - Bagci, Eyup; Elkiran, Omer; Evren, Harun (Asian Journal of Chemistry, 2013)
In this study, the essential oils of Helichrysum graveolens species from Turkey were investigated and 72 components were identified by GC, GC-MS. Essential oil was hydrodistilled by using Clevenger apparatus from the aerial parts of plants collected from the natural habitats. The essential oils yield is very low and 0.1 (v/w). Seventy two constituents were comprised the 82.97 % of the total essential oil extracted from the Helichrysum graveolens. The predominant compounds of Helichrysum graveolens were as alpha-cubebene (10.5 %), beta-caryophyllene (9.4 %), azulene-octahydro (7.5 %), caryophyllene oxide (8.2 %). The results were discussed in view of chemotaxonomy and natural products.
Keywords: Helichrysum graveolens; Asteraceae; Essential oil